2023
DOI: 10.3390/cancers15020329
|View full text |Cite
|
Sign up to set email alerts
|

A Subset of PD-1-Expressing CD56bright NK Cells Identifies Patients with Good Response to Immune Checkpoint Inhibitors in Lung Cancer

Abstract: (1) Despite the effectiveness of immune checkpoint inhibitors (ICIs) in lung cancer, there is a lack of knowledge about predictive biomarkers. The objective of our study is to analyze different subsets of T-lymphocytes and natural killer (NK) cells as predictive biomarkers in a cohort of patients with nonsmall cell lung cancer (NSCLC) treated with ICI. (2) This is an observational, prospective study with 55 NSCLC patients treated with ICI. A total of 43 T and NK cell subsets are analyzed in peripheral blood, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
(71 reference statements)
1
8
0
Order By: Relevance
“…This result indicates that NK CD56 brigh cells are not responsive to anti-PD-1 therapy and suggests that PD-1 expression on NK CD56 brigh cells could be upregulated by a compensatory mechanism triggered by therapy and could be related to response to therapy and/or vitiligo development. Consistently, it has been demonstrated a positive correlation between PD-1 expression on NK CD56 brigh cells and overall survival of patients with lung cancer undergoing immunotherapy ( 44 ). However, a higher number of patients should be considered to clarify this point.…”
Section: Discussionmentioning
confidence: 67%
“…This result indicates that NK CD56 brigh cells are not responsive to anti-PD-1 therapy and suggests that PD-1 expression on NK CD56 brigh cells could be upregulated by a compensatory mechanism triggered by therapy and could be related to response to therapy and/or vitiligo development. Consistently, it has been demonstrated a positive correlation between PD-1 expression on NK CD56 brigh cells and overall survival of patients with lung cancer undergoing immunotherapy ( 44 ). However, a higher number of patients should be considered to clarify this point.…”
Section: Discussionmentioning
confidence: 67%
“…Predictive markers have also been searched in the immune cell profiling [ 25 ], concluding that lymphocyte and NK cell populations are of great interest. However, no immune cell profile has yet been identified with sufficient clinical relevance to be established in clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…Growing studies have demonstrated that lymphocytes and NK cells are key roles in immune defense against tumor cells. A recent prospective study has identified a subset of circulating CD56+CD16‐PD‐1+ NK cells showing good predictive ability to ICIs response in NSCLC patients with immunotherapy 123 . In addition, considering cancer patients commonly inhibit deficiency in NK cells, growing evidence has indicated that adoptive transfer of NK cells could be a useful immunotherapy tool across a number of solid cancers 124–126 .…”
Section: Circulating Immune Cells In Antitumor Immunotherapymentioning
confidence: 99%
“…A recent prospective study has identified a subset of circulating CD56+CD16‐PD‐1+ NK cells showing good predictive ability to ICIs response in NSCLC patients with immunotherapy. 123 In addition, considering cancer patients commonly inhibit deficiency in NK cells, growing evidence has indicated that adoptive transfer of NK cells could be a useful immunotherapy tool across a number of solid cancers. 124 , 125 , 126 And beyond immunotherapy, researchers suggest that molecularly targeted agents can elicit NK cell‐mediated antitumor immunity, providing further evidence that NK cells will play an increasingly key role in cancer treatment.…”
Section: Circulating Immune Cells In Antitumor Immunotherapymentioning
confidence: 99%